2016
DOI: 10.1097/md.0000000000004164
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between indexed epicardial fat volume and coronary plaque volume assessed by cardiac multidetector CT

Abstract: We explored whether baseline indexed epicardial fat volume (EFVi) and serial changes in EFVi were associated with increase in coronary plaque volume as assessed by multidetector computed tomography.We retrospectively reviewed 87 patients with coronary artery plaque, identified during either baseline or follow-up cardiac computed tomography (CT) examinations. Each plaque volume was measured in volumetric units using a semiautomatic software tool. EFVi was quantified by calculating the total volume of epicardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Our findings show that iLAEAT is an independent predictor of AF burden and recurrence that may be clinically useful. Our hypothesis is supported by other investigations showing that indexed epicardial fat volume is tightly associated with major adverse cardiovascular events as well as coronary plaque volume ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings show that iLAEAT is an independent predictor of AF burden and recurrence that may be clinically useful. Our hypothesis is supported by other investigations showing that indexed epicardial fat volume is tightly associated with major adverse cardiovascular events as well as coronary plaque volume ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 90%
“…With regards to gestational weight gain, weight gains below the required amount for the products of conception have been hypothesized to be associated with delayed development via inadequate fetal growth or maternal ketosis 40 . Our previous results emphasis the importance of prenatal multi-micronutrients on increasing birthweight compared to the control group 21 , and the long-term effect of birthweight was also found on further intellectual development and physical growth 7 . In addition, postnatal nutritional factors, such as protein intake or breastfeeding, may also affect early child development 41 , 42 , although this pathway could be either biological or behavioral.…”
Section: Discussionmentioning
confidence: 58%
“…Recent research suggests that offspring of underweight mothers may also have impaired intellectual development. Maternal underweight is a known risk factor for low birth weight which is predictor of adverse brain development 6 , 7 . In addition, evidence from the US cohort study showed low pre-pregnancy BMI was associated with increased risk of delayed intellectual development of 2-year-old children 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…coronary ct angiography. Cardiac CT examinations were performed using a machine and protocol that we employed previously 19,24 . A prospective ECG tube current modulation technique were used.…”
Section: Echocardiographymentioning
confidence: 99%